PENGARUH PARTISIPASI ANGGARAN DAN PEMANFAATAN SISTEM INFORMASI KEUANGAN DAERAH TERHADAP KINERJA MANAJERIAL (STUDI PADA SKPD KOTA SINGKAWANG) - B41111147, Megawat1 B41111147 mega (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2015)
PENGARUH PARTISIPASI ANGGARAN DAN PEMANFAATAN SISTEM INFORMASI KEUANGAN DAERAH TERHADAP KINERJA MANAJERIAL (STUDI PADA SKPD KOTA SINGKAWANG) MEGAWATI Abstract The research aimed to examine and give empirical proof of 1) effect of budgetary participation on managerial performance. 2) effect of use information system of local government finance on managerial performance. 3) effect of budgetary participation and use of information system of local government finance on managerial performance. The research was causative study. The populations of the research were 32 SKPD in Singkawang. The data was conducted by using total sampling. The data was then analyzed by using multiple linear regression. The research findings showed that: 1) budgetary participation had positive effect but not significant on managerial performance. 2) the use of information system of regency’s finance had positive and significant impact on managerial performance. 3) budgetary participation and the use of information system of local government’s finance simultaneously had positive and significant effect on managerial work. Keywords: Managerial Performance, Budgetary Participation, Use of Information System of Local Government Finance.